2022
DOI: 10.1001/jamapediatrics.2022.2493
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Hospital-Acquired Harm Outcomes and Membership in a National Patient Safety Collaborative

Abstract: networks supported by the US Centers for Medicare & Medicaid Services Partnership for Patients program have reported significant reductions in hospital-acquired harm, but methodological limitations and lack of peer review have led to persistent questions about the effectiveness of this approach.OBJECTIVE To evaluate associations between membership in Children's Hospitals' Solutions for Patient Safety (SPS), a federally funded hospital engagement network, and hospital-acquired harm using standardized definition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…In this context, Coffey and colleagues aimed to evaluate the association between membership in Children’s Hospitals’ Solutions for Patient Safety (SPS), a hospital engagement network comprised of hospital partners in the USA and Canada, and hospital-acquired harm using standardised definitions and secular trend adjustment 19. Their prospective cohort study with historical controls harnessed interrupted time series analyses with staggered intervention introduction.…”
Section: Association Between Hospital-acquired Harm Outcomes and Memb...mentioning
confidence: 99%
“…In this context, Coffey and colleagues aimed to evaluate the association between membership in Children’s Hospitals’ Solutions for Patient Safety (SPS), a hospital engagement network comprised of hospital partners in the USA and Canada, and hospital-acquired harm using standardised definitions and secular trend adjustment 19. Their prospective cohort study with historical controls harnessed interrupted time series analyses with staggered intervention introduction.…”
Section: Association Between Hospital-acquired Harm Outcomes and Memb...mentioning
confidence: 99%
“…It is only through hard work to develop new processes of care coupled with efforts to implement changes and bake those changes into the culture of health care that we will continue to move forward. The study by Coffey et al shows that forward movement is possible. Let us all build off of the hope this finding brings and reinvigorate our efforts to truly get to zero harm.…”
mentioning
confidence: 99%
“…First, it is important to recognize that while not all of the reductions seen are clearly causally attributable to the HEN intervention, the finding of improvement over time in 7 of 8 patient safety measures, regardless of cause, is remarkable. While some prior studies have suggested improvements after many years of hard work in adverse event rates for certain discrete conditions, hospital-wide rates of harms both in hospitals generally and in pediatric hospitals in particular appeared not to be improving in the years before the study by Coffey et al While the 8 serious safety events (SSEs) the authors followed are not a representative sample of all harms, they are some of the highest profile harms in hospitals and have been the focus of major patient safety improvement efforts. It is extremely encouraging to see data suggesting that work beginning to pay off, whether this is the result of the SPS’s work alone or the combined effect of the SPS plus one or more of the many concurrent, widespread efforts to improve safety, including high-reliability health care initiatives, reductions in resident-physician extended work shifts, changes in nurse workloads, or efforts to improve handoffs and communication on family-centered rounds, to name just a few.…”
mentioning
confidence: 99%
See 2 more Smart Citations